2002
DOI: 10.1046/j.0022-0477.2001.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal tolerance as therapy of type I allergy: intranasal application of recombinant Bet v 1, the major birch pollen allergen, leads to the suppression of allergic immune responses and airway inflammation in sensitized mice

Abstract: Background Several studies have demonstrated that mucosal administration of soluble antigens can prevent the onset or reduce the severity of certain autoimmune diseases or allergies. Few studies exist showing the ef®cacy of mucosal tolerance for therapy of such diseases. Objective The aim of the present study was to modulate an allergic immune response by intranasal antigen administration in an already sensitized organism. Methods A murine model of allergic asthma to birch pollen (BP) and its major allergen Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 41 publications
3
47
0
1
Order By: Relevance
“…As examples, intranasal application of recombinant birch allergen Bet v1 led to the suppression of the allergic immune response in sensitized mice (56), and continuous intranasal exposure to OVA in sensitized BALB/c animals led to the complete abrogation of airway inflammation (53). However, the effectiveness of mucosal OVA administration in suppressing T-cell immunity declined when mucosal antigen delivery started after immunization and became selective for the Th2-mediated pulmonary allergic response but not for T-cell-mediated antibody production (29).…”
Section: Discussionmentioning
confidence: 99%
“…As examples, intranasal application of recombinant birch allergen Bet v1 led to the suppression of the allergic immune response in sensitized mice (56), and continuous intranasal exposure to OVA in sensitized BALB/c animals led to the complete abrogation of airway inflammation (53). However, the effectiveness of mucosal OVA administration in suppressing T-cell immunity declined when mucosal antigen delivery started after immunization and became selective for the Th2-mediated pulmonary allergic response but not for T-cell-mediated antibody production (29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the local increment of IgA in response to LNIT may contribute to its improved effectiveness in protecting Th2-sensitized mice from airway allergen challenge. With respect to the use of recombinant allergens for mucosal tolerance induction as a treatment strategy against allergic sensitization, it has been shown in a murine model of birch pollen allergy that intranasal application of recombinant Bet v 1 (the major birch pollen allergen) led to significant responses in naive and in sensitized mice [27]; more importantly, the immunosuppression effect of LNIT with rBet v 1 was able to be directed against rBet v 1 itself, as well as towards the whole pollen [28]. In our study, similar results were found for LNIT with rDer p 2 in conjunction with FIP which did not only downregulate rDer p 2-sensitized mice but also those mice sensitized by Der p.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-g was measured by ELISA as previously described [23]. All other cytokines were measured with commercially available mouse ELISA kits; IL-4 and IL-5 (Endogen, Woburn, MA, USA), IL-13 and eotaxin (R & D Systems, MN, USA), with sensitivities of < 5 pg/ml for IL-4 and IL-5, < 1·5 pg/ml for IL-13 and < 3 pg/ml for eotaxin.…”
Section: Cytokine Analysismentioning
confidence: 99%